The Influence Of Price, Product Quality And Service Quality On Purchase Decision Of Netflix Applications - Waseso Segoro; Mochamad Rifky Rifaldi (Publisher Cv. Inara, 2021)
This study aims to determine the effect of price, product quality and service quality on purchasing decisions partially and simultaneously or collectively. After knowing the magnitude of the influence of the three independent variables, we will find the variable that most influences the purchase decision on the Netflix application. This study uses a purposive sampling technique which is included in the type of non-probability sampling, by distributing questionnaires to consumers of Netflix products who have bought and experienced Netflix products as many as 101 respondents. In this study using the SPSS 25 program with the analytical tools used are the Validity and Reliability Test, Multiple Linear Regression Analysis, Normality Test, Multicollinearity Test and Heteroscedasticity Test. The result of the multiple linear regression model is Y = 2. 031 + 0.133X1 + 0.263X2 + 0.357X3 and analysis shows that simultaneously there is an influence between price, product quality and service quality on purchasing decisions on the Netflix application. In addition, it was found that the R2 value was 0.567 or 56.7% and the remaining 43.3% was explained or influenced by other variables not included in this study.